When Quranic Learning Goes Online: The Phenomenon of Yusuf Mansur in Da’wah Marketing Facing the Covid-19 Pandemic - Aripudin, Acep (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
The Covid-19 (Corona viruses) pandemic has forced the system for spreading and understanding the Qur'an to be carried out online. Online media, such as e-learning, was known before the corona viruses season. One of the institutions implementing e-learning is the Darul Qur'an Islamic Boarding School, led by Yusuf Mansur. The famous preacher with the "alms flag as the gateway to riches" is phenomenal in Indonesia. This study uses the phenomenological method and the AIC (attract inform community) model, combining techniques based on social research and Information Technology (IT). This article proves that Mansur was able to build a system for disseminating the Qur’an (online and offline/face to face) combined with a business concept with floating funds and cooperatives and a tower with 285 rooms. Based on the AIC model, it can be stated that Mansur's PPPA web (Qur’an memorizing nursery program) was effective in supporting e-learning and socializing the Qur’an during the Covid-19 period. The Qur'anic e-learning approach has implications for Islamic institutions as capital for brand marketing of da'wah institutions and their development. This strategy is a solution to spreading the Qur'an in abnormal situations and experiences in the future.